Application of NMR Logging in the Evaluation of Gulong Shale Oil - CHEN Longchuan; ZHANG Zhaoqian; ZHENG Jiandong; WANG Chunyan; ZHU Jianhua; WANG Wenjuan; GAO Jifeng (Cejing jishu)
Gulong shale oil reservoir has a high clay content, complex pore structure, and developed micro-nano pore throats and micro fractures. It is difficult to evaluate the characterization of reservoir pore structure, physical properties, and oil content using conventional methods. In response to the above difficulties, based on rock physics experiments, a nuclear magnetic resonance (NMR) T2 cutoff effective porosity calculation method and a 2D NMR oil saturation calculation model considering small pore oil content are proposed. Through NMR interval porosity analysis, the pore structure of the Gulong shale reservoir is clarified. The average relative error of effective porosity calculated by the above method is 7.3%, and the average absolute error of oil saturation is 4.0%. This method improves the interpretation accuracy of key parameters submitted for reserves, also provides technical support for reserve calculation and development plan preparation and implementation. These technical processes and methods also have guiding significance for evaluating the effective porosity and oil saturation of shale oil, and the research content can help promote the development and utilization of unconventional oil and gas resources such as shale oil.